Controlled concrete demolition using expansive cracking agents. - Gambatese, John A. (Journal of construction engineering and management)
The demolition of concrete is a common part of many renovation and rehabilitation projects in the construction industry. Traditional means for demolishing concrete include the use of kackhammers, explosives, and high-pressure water blasting. On some projects, it may required to confine the demolition to a small of the structure or to a shallow depth on a concrete member. If this is the case, the use of traditional demolition methods may not be feasible or may require special precautions and procedures. A pilot study was conducted to evaluate the use of a soundless chemical demolition agent (SCDA) for performing controlled concrete demolition on a small scale. SCDAs are dry, powdery materials that expand considerably when mixed with water. The agents have traditionally been used for large demolition applications such as for mining and for breaking up foundations. The study examined the performance of SCDA on a small scale, placing SCDA in holes 6.35 mm (1/4 in). in diameter and less. The results of the study indicate that SCDA can be used on a small scale to create the controlled cracking of concrete. Using SCDA in this manner can be useful for undertaking controlled demolition without excessive vibrations, loud noise, or water. Examples of useful applications include removing just the cover from concrete structures and demolishing sections of concrete features that are of architectural or historic significance.